Decade of experimental permafrost thaw reduces turnover of young carbon and increases losses of old carbon, without affecting the net carbon balance - Olid, Carolina; Klaminder, Jonatan; Monteux, Sylvain; Johansson, Margareta; Dorrepaal, Ellen (Global change biology, 2020)
Thicker snowpacks and their insulation effects cause winter‐warming and invoke thaw of permafrost ecosystems. Temperature‐dependent decomposition of previously frozen carbon (C) is currently considered one of the strongest feedbacks between the Arctic and the climate system, but the direction and magnitude of the net C balance remains uncertain. This is because winter effects are rarely integrated with C fluxes during the snow‐free season and because predicting the net C balance from both surface processes and thawing deep layers remains challenging. In this study, we quantified changes in the long‐term net C balance (net ecosystem production) in a subarctic peat plateau subjected to 10 years of experimental winter‐warming. By combining 210Pb and 14Cdating of peat cores with peat growth models, we investigated thawing effects on year‐round primary production and C losses through respiration and leaching from both shallow and deep peat layers. Winter‐warming and permafrost thaw had no effect on the net C balance, but strongly affected gross C fluxes. Carbon losses through decomposition from the upper peat were reduced as thawing of permafrost induced surface subsidence and subsequent waterlogging. However, primary production was also reduced likely due to a strong decline in bryophytes cover while losses from the old C pool almost tripled, caused by the deepened active layer. Our findings highlight the need to estimate long‐term responses of whole‐year production and decomposition processes to thawing, both in shallow and deep soil layers, as they may contrast and lead to unexpected net effects on permafrost C storage. Thicker snowpacks cause winter‐warming and invoke thawing of permafrost ecosystems. Decomposition of previously frozen carbon (C) may cause a strong positive feedback to the climate system, but the magnitude of the permafrost C loss remains uncertain. We investigated the long‐term effects of winter‐warming on the C balance of a permafrost‐containing peatland subjected to a 10 years snow manipulation experiment. Winter‐warming did not affect the net C balance regardless of the increased old C losses. This small overall effect was due to a strong decrease in young C losses associated with the new water saturated conditions and the decline in bryophytes.